The expression of Matrix metalloproteinase-2 and cyclooxygenase-2 by immunohistochemistry in patients with colorectal carcinoma - Hussein, Areej A.; Ibrahim, Basim M.; Kashman, Basim M. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Human colorectal carcinogenesis is a complex, multistep and multigenetic process. Matrix metalloproteinase-2 and cyclooxygenase-2 are key enzyme in degradation of extracellular material, are over expressed in several epithelia like colorectal adenocarcinoma.Objectives: This study was designed to detect the expression of matrix metalloproteinase-2 and cyclooxygenase-2 in patients with colorectal carcinoma and their correlation with age, gender, tumor grade and presence or absence of muscle invasion.Materials and methods: Immunohistochemical staining of MMP-2 and COX-2 was determined in 40 tissue samples from colorectal patients, from teaching laboratories in Baghdad medical city. In addition twelve apparently normal colorectal autopsies were used as a control group.Results: The expression of matrix metalloproteinase-2 was detected in 30 of 40 colorectal cancer cases (75%) while cyclooxygenase-2 was detected in 31 0f 40 colorectal cancer cases (77.5%). All normal colorectal specimens showed negative results. The incidence of both of them was higher for grade II than those in earlier grade.Conclusion: Cancer cells to have a more aggressive behavior may show an up regulation of tumor cell derived matrix metalloproteinase-2 and cyclooxygenase-2.